Mechanochemical Synthesis of New Praziquantel Cocrystals - Mureşan-Pop, Marieta (2024)
The authors acknowledge Fundac\u0327a\u0303o para a Cie\u0302ncia e a Tecnologia, and FEDER, Portugal 2020, and Lisboa 2020 for funding (project LISBOA-01-0145-FEDER-030988). Financial support is also acknowledged from grant POWR.03.02.00-00-I026/16 co-financed by the European Union through the European Social Fund under the Operational Program Knowledge Education Development and from Adam Mickiewicz University for the funds from the Initiative of Excellence Research University (ID-UB) program.This work is a contribution to the COST Action CA18112-Mechanochemistry for Sustainable Industry. Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.